Assessment of influence of traditional cardiovascular risk factors and inflammation on arterial wall structural characteristics in psoriatic arthritis - T V Korotaeva; E Y Loginova; E S Mach; D S Novikova; E N Alexandrova; E L Nasonov; N N Firsov (Научно-практическая ревматология)
Assessment of influence of traditional cardiovascular risk factors and inflammation on arterial wall structural characteristics in psoriatic arthritis. Objective. To assess possibility of traditional cardiovascular risk (CVR) factors application as markers of subclinical atherosclerosis in pts with psoriatic arthritis (PA). Material and methods. 130 pts with PA (51 male and 79 female) without clinical signs of coronary heart disease (CHD) and stroke. were included. Mean age was 43 years (39-48 years), mean PA duration – 7 years (2 months-42 years), mean psoriasis duration – 15 years (5,5 – 26 years). PA activity was assessed with DAS4. Age, total cholesterol (TC), high density lipoprotein (HDLP), low density lipoprotein (LDLP), C-reactive protein (CRP), fibrinogen, systolic blood pressure, body mass index (BMI), atherogenity coefficient (AC), relative risk of CHD development, presence of diabetes and smoking were evaluated. Mean and maximal intima-media complex thickness (IMCT) of common carotid arteries was examined with duplex scanning. Results. TC, LDLP and AC elevation was revealed in all and BMI elevation – in one third of pts. In 55% of pts CVR was mean and higher, in 23,5% CVR was absent and in 21,5% CVR was below mean. CVR significantly correlated with mean and maximal carotid arteries IMCT (R=0,48, p<0,00001 and R=0,41, p<0,00001) and fibrinogen (R=0,22, p<0,011). In women CVR correlated with fibrinogen (R=0,27, p<0,16), BMI (R=0,35, p<0,16), mean and maximal carotid arteries IMCT (R=0,50, p<0,00001 and R=0,38, p<0,0005 respectively) and psoriasis duration (R=0,30, p<0,006). In men CVR did not correlated with fibrinogen. CVR did not correlated with DAS4 and CRP. Conclusion. CVR in PA is not connected with traditional markers of inflammation andindex of clinical disease activity.